An Algorithm for Solving Integer Goal Programming Problems with Fuzzy Parameters - Khaled Elsharkawy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we describe an algorithm for modeling and solving integer linear goal programming problems with fuzzy parameters. The proposed algorithm helps the decision maker and the analyst in determination the aspiration levels of the goals by a method based on the feasible domain, the differential weights of the sub-goals and the decision maker’s preferences. The solution, which is obtained by the present algorithm, is most preferred by the decision maker. An illustrative example is presented.